Hubungan Pengetahuan, Pola Asuh Pemberian Makan Dan Sanitasi Lingkungan Terhadap Kejadian Stunting Balita Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Buhit Kabupaten Samosir Tahun 2025 - Siboro , Vinny Aslinar; Rochadi , Kintoko; Sinaga, Janno; Manurung, Kesaktian; Bancin , Dewi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Stunting is a chronic nutritional problem with profound implications for the quality of human resources. Multiple factors, including parental knowledge, feeding practices, and environmental sanitation, influence this condition. The working area of the Buhit Community Health Center (Puskesmas Buhit) in Samosir Regency continues to face challenges in addressing stunting, making the identification of dominant factors essential for targeted interventions. Objective: This study aims to analyze the relationship between parental knowledge, feeding practices, and environmental sanitation with the incidence of stunting among children aged 24–59 months, and to identify the most influential factor in the Buhit Community Health Center service area, Samosir Regency, in 2025. Methods: This research employed an observational analytic design with a cross-sectional approach. The study population comprised all children aged 24–59 months (n = 577). A total of 88 respondents were selected using simple random sampling and the Slovin formula. Data were collected through questionnaires and anthropometric measurements, and analyzed using Chi-square tests and logistic regression. Results: Bivariate analysis revealed a significant association between parental knowledge (p = 0.000), feeding practices (p = 0.000), and environmental sanitation (p = 0.004) and the incidence of stunting. Multivariate analysis revealed that feeding practices were the most dominant factor (OR = 105.463; 95% CI = 13.888–800.848). This indicates that children with inadequate feeding practices have a 105.463-fold higher risk of stunting compared to those with good feeding practices. Conclusion: A significant relationship exists between parental knowledge, feeding practices, environmental sanitation, and the incidence of stunting. The most dominant factor is feeding practices. Therefore, stunting prevention interventions in this area should focus on improving parents’ understanding and implementation of appropriate feeding practices.